A method for preparing ultrafine-grained biodegradable magnesium alloy wire
Ultrafine crystal biodegradable magnesium alloy wires are prepared through large deformation extrusion and low temperature thermal drawing processes, which solves the problem of excessively rapid corrosion of magnesium alloys in the body, improves production efficiency and corrosion resistance of the wires, and meets the application needs of implanted materials.
Patent Information
- Application Number
- CN202311282256.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-07
- Publication Date
- 2025-04-08
AI Technical Summary
Existing magnesium alloys corrode too quickly in the body, produce bubbles, and affect mechanical stability, limiting their application in instruments such as staples.
Ultrafine crystalline biodegradable magnesium alloy wire is prepared by large deformation extrusion and low temperature thermal drawing processes. The grain size and corrosion behavior are controlled through solid solution treatment, ingot pre-extrusion, extrusion wire, low temperature drawing and annealing.
It effectively reduces the pull-out passes, improves production efficiency, enhances the plasticity and corrosion resistance of the silk material, meets the corrosion rate requirements of the implanted material, and avoids the damage and economic burden of secondary surgery.
Smart Images

Figure CN119771952A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, and in particular to a method for preparing ultrafine-grained biodegradable magnesium alloy wires. Background Art
[0002] Biodegradable metal materials refer to new medical metal materials that can be naturally absorbed or excreted by the human body in a body fluid environment and have no adverse reactions to the human body. They mainly include iron alloys, magnesium alloys, and zinc alloys. Among them, magnesium alloys have good biocompatibility and biodegradability and have good application prospects. At present, bone repair magnesium alloys in many countries have been approved to enter clinical research.
[0003] An anastomosis stapler is a medical device used to connect broken or removed tissues and organs. It is widely used in gastrointestinal, vascular, neurological and other surgical operations.
[0004] Therefore, the material properties of magnesium alloys, which are both degradable and have good mechanical properties and biocompatibility, are of great clinical significance for the preparation of biodegradable staples. However, magnesium and its alloys also have problems such as excessive corrosion, bubble generation, and influence on mechanical stability in the body, which limit their application in instruments such as staples. In order to improve the degradation behavior of magnesium and its alloys in the body, the main methods currently used are changing the composition, regulating the organizational structure, and applying surface treatment. Among them, changing the composition is to change the chemical properties and phase composition of the magnesium alloy by adding other elements, thereby affecting its corrosion potential and current density; regulating the organizational structure is to change the corrosion morphology and mechanism by controlling the grain size, phase distribution and defect state of the magnesium alloy; applying surface treatment is to form a protective layer or functional layer by coating or depositing other materials, thereby inhibiting or regulating the corrosion rate of the magnesium alloy. However, the existing method requires multiple drawing when extruding the wire, and frequent annealing is required during the drawing process, which is inefficient, and the wire is prone to microcracks and work hardening during the cold drawing process. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a method for preparing ultrafine-grained biodegradable magnesium alloy wire, which solves the problems raised in the background technology.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a method for preparing ultrafine-grained biodegradable magnesium alloy wire, the material component content Zn: 1.75%-6.25%, impurity content ≤0.03%, and the remaining component is Mg.
[0007] Preferably, the method steps include the following:
[0008] S1: subjecting the raw materials to solution treatment at a temperature of 400±5°C for 12 hours, followed by water cooling to room temperature;
[0009] S2: Pre-extrude the raw material into an ingot and initially extrude the raw material into an extruded rod with a diameter of 20 mm;
[0010] S3: Extrude the extruded rod into a wire with a diameter of 1.0 mm at a temperature of 400°C, and use a large extrusion ratio to refine the grains so that the extruded wire has good plastic deformation ability, which is beneficial to the subsequent drawing process;
[0011] S4: Special magnesium alloy wire drawing equipment can be used for low temperature hot drawing at 120-250℃ to a size of 0.1-0.5mm, with a cumulative deformation of 50%-60%, which can avoid frequent annealing during the drawing process;
[0012] S5: After reaching the required size, anneal at 250-260℃ for 20 minutes to eliminate the stress generated during the extrusion and drawing process. Only one annealing is performed to keep the wire in good forming performance and corrosion resistance.
[0013] Preferably, the raw materials in S2 also need to be preheated during the ingot pre-extrusion process.
[0014] Preferably, after the ingot is pre-extruded out of the mold in S2, it also includes a homogenization treatment, and the obtained extruded rod ingot is sent to a box-type resistance furnace and heated to 450-500°C for homogenization, and kept warm for 6-8h, and then taken out of the furnace and first water-cooled at a cooling rate of 5-7°C / s, then air-cooled, and then water-cooled at a cooling rate of 2-4°C / s, and finally air-cooled to ambient temperature.
[0015] Preferably, the step S3 further comprises treating the oxide layer on the surface of the extruded rod pre-extruded from the ingot, and the steps for treating the oxide layer on the surface of the extruded rod are as follows:
[0016] S01: Clean the extrusion rod. Use a detergent to clean the extrusion rod to ensure that there is no impurities such as oil, dust, degreasing agent, etc. on the surface;
[0017] S02: Solution treatment, placing the treated extruded rods in a solution containing acidic, alkaline or neutral chemicals for treatment; the treatment time and temperature depend on the type of solution and the properties of the extruded rods; this step can remove the oxide scale on the surface of the extruded rods, making the surface of the extruded rods more uniform, and improving the appearance quality and corrosion resistance.
[0018] Preferably, the raw material is solution treated by placing the magnesium alloy material into a microwave-assisted heat treatment furnace and performing the solution treatment in a microwave field. Before the magnesium alloy solution treatment, the interior of the furnace cavity needs to be preheated by resistance wire heating at a preheating temperature of 5°C / min.
[0019] Preferably, the solution treatment of the magnesium alloy material, casting or ingot is carried out in a microwave field, and the microwave application frequency is 1-3 GHz and the power is 2000-3000W.
[0020] Preferably, the inner wall of the extrusion die in S2 is lubricated with graphite, which can provide a better lubrication effect at high temperature due to the high temperature stability and low volatility of the solid lubricant.
[0021] Preferably, the internal lubrication of the mold can also be achieved by coating a lubricating coating, such as a molybdenum coating or a titanium coating, on the surface of the mold to reduce the contact between the metal surfaces and thereby reduce the wear.
[0022] The present invention provides a method for preparing ultrafine-grained biodegradable magnesium alloy wire.
[0023] Beneficial effects:
[0024] 1. The large deformation extrusion adopted in the present invention can directly extrude relatively fine wire (diameter 1.0mm), which can effectively reduce the number of subsequent drawing passes. The wire is drawn at a low temperature of 200-250°C during the drawing process. After the processing is completed, the annealing process can be omitted, which can greatly improve the production efficiency. At the same time, the wire can have better plasticity and corrosion resistance, meeting the requirements of the implant material for the corrosion rate;
[0025] 2. Drawing uses a special equipment to heat the continuous drawing process. One drawing can accumulate 50%-60% deformation, and frequent annealing can be avoided during the drawing process. Wire with a diameter of 0.1-0.5mm can be obtained after 2 to 3 continuous drawing passes, which greatly improves the processing efficiency of the wire. The equipment that can heat the drawing avoids the problem of micro cracks and work hardening in the wire during the cold drawing process, and improves the surface quality and yield rate of the wire;
[0026] 3. The large plastic deformation during extrusion and drawing can effectively refine the grain size of magnesium alloy wire, thereby improving the comprehensive performance of the alloy. The final grain size is about 5-10μm, the tensile strength reaches 280MPa, and the elongation at break is ≥20%. At the same time, heating during the drawing process enables the wire to obtain good plasticity and corrosion resistance under the condition of high strength, and can effectively refine the grain of the wire, which is beneficial to further improve the mechanical strength and corrosion resistance of magnesium-based alloys;
[0027] 4. The present invention is a biodegradable material. After being made into anastomotic staples and implanted in the body, it can be naturally degraded in the body after achieving the medical effect, avoiding the damage and economic burden caused by secondary surgery. The wire component design avoids the use of Al and rare earth metals. Al has chronic neurotoxicity, and the biosafety of the material is guaranteed from the selection of materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the process of the present invention;
[0029] Figure 2 This is a schematic diagram of the relationship between stress and strain in Example 4 of the present invention;
[0030] Figure 3 Schematic diagram of the relationship between stress and strain in Example 3 of the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Embodiment 1:
[0033] A method for preparing ultrafine-grained biodegradable magnesium alloy wire, wherein the material component is 2.25%, the impurity component is ≤0.03%, and the remaining component is Mg.
[0034] The method steps include the following:
[0035] S1: subjecting the raw materials to a solution treatment at a temperature of 395°C for 12 hours, followed by water cooling to room temperature;
[0036] S2: Pre-extrude the raw material into an ingot and initially extrude the raw material into an extruded rod with a diameter of 20 mm;
[0037] S3: Extrude the extruded rod into a wire with a diameter of 1.0 mm at a temperature of 400°C, and use a large extrusion ratio to refine the grains so that the extruded wire has good plastic deformation ability, which is beneficial to the subsequent drawing process;
[0038] S4: Special magnesium alloy wire drawing equipment can be hot drawn at 250℃ to 0.5mm size, with a cumulative deformation of 60%, which can avoid frequent annealing during the drawing process;
[0039] S5: After reaching the required size, anneal at 260℃ for 20min to eliminate the stress generated during the extrusion and drawing process. Only one annealing is performed to keep the wire in good forming performance and corrosion resistance.
[0040] The raw materials in S2 also need to be preheated during the ingot pre-extrusion process.
[0041] After the ingot is pre-extruded out of the mold in S2, it also includes a homogenization treatment, and the obtained extruded rod ingot is sent to a box-type resistance furnace and heated to 500°C for homogenization, and kept warm for 8 hours, and then taken out of the furnace, first water-cooled at a rate of 7°C / s, then air-cooled, and then water-cooled at a rate of 4°C / s, and finally air-cooled to ambient temperature.
[0042] The step S3 also includes treating the oxide layer on the surface of the extruded rod pre-extruded from the ingot, and the steps for treating the oxide layer on the surface of the extruded rod are as follows:
[0043] S01: Clean the extrusion rod. Use a detergent to clean the extrusion rod to ensure that there is no impurities such as oil, dust, degreasing agent, etc. on the surface;
[0044] S02: Solution treatment, placing the treated extruded rods in a solution containing acidic, alkaline or neutral chemicals for treatment; the treatment time and temperature depend on the type of solution and the properties of the extruded rods; this step can remove the oxide scale on the surface of the extruded rods, making the surface of the extruded rods more uniform, and improving the appearance quality and corrosion resistance.
[0045] The raw materials are solution treated by placing the magnesium alloy material into a microwave-assisted heat treatment furnace and performing the solution treatment in a microwave field. Before the magnesium alloy solution treatment, the interior of the furnace cavity needs to be preheated by resistance wire heating. The preheating temperature is 250°C and the heating rate is 200°C.
[0046] The solution treatment of the magnesium alloy material, casting or ingot is carried out in a microwave field, and the microwave application frequency is 3 GHz and the power is 3000 W.
[0047] The inner wall of the extrusion die in S2 is lubricated with graphite, and the high temperature stability and low volatility of the solid lubricant can provide a better lubrication effect at high temperatures.
[0048] Internal lubrication of the mold can also be achieved by applying a lubricating coating, such as molybdenum coating or titanium coating, on the mold surface to reduce contact between metal surfaces and reduce wear.
[0049] Embodiment 2:
[0050] A method for preparing an ultrafine-grained biodegradable magnesium alloy wire material, wherein the material component content is Zn: 1.75%, the impurity component is ≤0.03%, and the remaining component is Mg.
[0051] The method steps include the following:
[0052] S1: subjecting the raw materials to solution treatment at a temperature of 405°C for 12 hours, followed by water cooling to room temperature;
[0053] S2: Pre-extrude the raw material into an ingot and initially extrude the raw material into an extruded rod with a diameter of 20 mm;
[0054] S3: Extrude the extruded rod into a wire with a diameter of 1.0 mm at a temperature of 400°C, and use a large extrusion ratio to refine the grains so that the extruded wire has good plastic deformation ability, which is beneficial to the subsequent drawing process;
[0055] S4: Special magnesium alloy wire drawing equipment can be used for low temperature hot drawing at 120℃ to a size of 0.1mm, with a cumulative deformation of 50%, which can avoid frequent annealing during the drawing process;
[0056] S5: After reaching the required size, anneal at 250-260℃ for 20 minutes to eliminate the stress generated during the extrusion and drawing process. Only one annealing is performed to keep the wire in good forming performance and corrosion resistance.
[0057] After the ingot is pre-extruded out of the mold in S2, it also includes a homogenization treatment, and the obtained extruded rod ingot is sent to a box-type resistance furnace and heated to 450°C for homogenization, and kept warm for 6 hours, and then taken out of the furnace, first water-cooled at a rate of 5°C / s, then air-cooled, and then water-cooled at a rate of 2°C / s, and finally air-cooled to ambient temperature.
[0058] The step S3 also includes treating the oxide layer on the surface of the extruded rod pre-extruded from the ingot, and the steps for treating the oxide layer on the surface of the extruded rod are as follows:
[0059] S01: Clean the extrusion rod. Use a detergent to clean the extrusion rod to ensure that there is no impurities such as oil, dust, degreasing agent, etc. on the surface;
[0060] S02: Solution treatment, placing the treated extruded rods in a solution containing acidic, alkaline or neutral chemicals for treatment; the treatment time and temperature depend on the type of solution and the properties of the extruded rods; this step can remove the oxide scale on the surface of the extruded rods, making the surface of the extruded rods more uniform, and improving the appearance quality and corrosion resistance.
[0061] The raw materials are solution treated by placing the magnesium alloy material into a microwave-assisted heat treatment furnace and performing the solution treatment in a microwave field. Before the magnesium alloy solution treatment, the interior of the furnace cavity needs to be preheated by resistance wire heating at a preheating temperature of 200°C and 5°C / min.
[0062] The solution treatment of the magnesium alloy material, casting or ingot is carried out in a microwave field, and the microwave application frequency is 1 GHz and the power is 2000W.
[0063] The inner wall of the extrusion die in S2 is lubricated with graphite, and the high temperature stability and low volatility of the solid lubricant can provide a better lubrication effect at high temperatures.
[0064] Internal lubrication of the mold can also be achieved by applying a lubricating coating, such as molybdenum coating or titanium coating, on the mold surface to reduce contact between metal surfaces and reduce wear.
[0065] Embodiment 3:
[0066] The ingot with a diameter of 40mm is extruded into a cylindrical billet with a diameter of 20mm at 400℃. After removing the surface oxide layer of the cylindrical billet, it is extruded into a magnesium alloy wire with a diameter of 1mm at 400℃. The inner wall of the extrusion die is lubricated with graphite. The extruded magnesium wire is continuously drawn at a temperature of 200-230℃ with a deformation of 5%-20% per pass to a diameter size of 0.35mm, and the cumulative deformation is 87%. The wire with a diameter of 0.35mm is subjected to stress relief annealing at 200-240℃ for 20min. The tensile strength of the wire is 288MPa, the elongation at break is 33%, and the grain size is 1-5μm. Figure 3 shown.
[0067] Embodiment 4:
[0068] After the ingot is solution treated at 400°C for 12 hours, it is rapidly cooled in water, and the ingot with a diameter of 40 mm is extruded into a cylindrical billet of 30 mm at 400°C. After the surface oxide layer of the cylindrical billet is removed, it is extruded into a magnesium alloy wire with a diameter of 1.0 mm at 400°C, and the inner wall of the extrusion die is lubricated with graphite. The extruded magnesium wire is continuously drawn at 220°C with a deformation of 10% per pass to a diameter of 0.27 mm, and the cumulative deformation is 94%. The wire with a diameter of 0.27 mm is stress-relieved and annealed at 200-240°C for 20 minutes. The tensile strength of the wire is 295 MPa, the elongation at break is 31%, and the grain size is 1-5 μm. Figure 2 shown.
[0069] Embodiment 5:
[0070] The difference from Example 4 is that the wire with a diameter of 1.0 mm is extruded at a temperature of 350° C. and finally drawn into a magnesium alloy wire with a diameter of 0.27 mm. The tensile strength of the wire reaches 304 MPa and the elongation at break reaches 27%.
[0071] The large deformation extrusion adopted by the present invention can directly extrude relatively fine wire (diameter 1.0mm), which can effectively reduce the number of subsequent drawing passes. The wire adopts 200-250℃ low-temperature drawing during the drawing process. The annealing process can be omitted after the processing is completed, which can greatly improve the production efficiency. At the same time, the wire can have better plasticity and corrosion resistance, and meet the requirements of the implant material for the corrosion rate; the drawing uses a special equipment heating continuous drawing process, and a drawing can accumulate 50%-60% of the deformation, and frequent annealing during the drawing process can be avoided in the middle. After 2 to 3 continuous drawing passes, a wire with a diameter of 0.1-0.5mm can be obtained, which greatly improves the processing and production efficiency of the wire. The equipment that can heat the drawing avoids the problem of easy generation of microcracks and work hardening of the wire during the cold drawing process, and improves the wire. Surface quality and yield rate; large plastic deformation during extrusion and drawing can effectively refine the grain size of magnesium alloy wire, thereby improving the comprehensive performance of the alloy, and the final grain size is about 5-10μm, the tensile strength reaches 280MPa, and the elongation at break is ≥20%. At the same time, heating during the drawing process enables the wire to obtain good plasticity and corrosion resistance under the condition of high strength, and at the same time can effectively refine the grain of the wire, which is beneficial to further improve the mechanical strength and corrosion resistance of the magnesium-based alloy; the present invention is a biodegradable material, which can be made into anastomotic nails and implanted in the body. After achieving the medical effect, it can be naturally degraded in the body, avoiding the damage and economic burden caused by secondary surgery. The wire composition design avoids the use of Al and rare earth metals. Al has chronic neurotoxicity, and the biosafety of the material is guaranteed from the selection of materials.
[0072] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0073] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing ultrafine-grained biodegradable magnesium alloy wire, characterized in that: The material composition content is Zn: 1.75%-6.25%, the impurity content is ≤0.03%, and the remaining component is Mg.
2. The method for preparing ultrafine-grained biodegradable magnesium alloy wire according to claim 1, characterized in that: The method steps include the following: S1: subjecting the raw materials to solution treatment at a temperature of 400±5°C for 12 hours, followed by water cooling to room temperature; S2: Pre-extrude the raw material into an ingot and initially extrude the raw material into an extruded rod with a diameter of 20 mm; S3: Extrude the extruded rod into a wire with a diameter of 1.0 mm at a temperature of 400°C, and use a large extrusion ratio to refine the grains so that the extruded wire has good plastic deformation ability, which is beneficial to the subsequent drawing process; S4: Special magnesium alloy wire drawing equipment can be used for low temperature hot drawing at 120-250℃ to a size of 0.1-0.5mm, with a cumulative deformation of 50%-60%, which can avoid frequent annealing during the drawing process; S5: After reaching the required size, anneal at 250-260℃ for 20 minutes to eliminate the stress generated during the extrusion and drawing process. Only one annealing is performed to keep the wire in good forming performance and corrosion resistance.
3. The method for preparing ultrafine-grained biodegradable magnesium alloy wire according to claim 1, characterized in that: The raw materials in S2 also need to be preheated during the ingot pre-extrusion process.
4. The method for preparing ultrafine-grained biodegradable magnesium alloy wire according to claim 1, characterized in that: The step S3 also includes treating the oxide layer on the surface of the extruded rod pre-extruded from the ingot, and the steps for treating the oxide layer on the surface of the extruded rod are as follows: S01: Clean the extrusion rod. Use a detergent to clean the extrusion rod to ensure that there is no impurities such as oil, dust, degreasing agent, etc. on the surface; S02: Solution treatment, placing the treated extruded rods in a solution containing acidic, alkaline or neutral chemicals for treatment; the treatment time and temperature are determined according to the type of solution and the properties of the extruded rods; This step can remove the oxide scale on the surface of the extruded rod, making the surface of the extruded rod more uniform, improving the appearance quality and corrosion resistance.
5. The method for preparing ultrafine-grained biodegradable magnesium alloy wire according to claim 1, characterized in that: The raw materials are subjected to solution treatment by placing the magnesium alloy material into a microwave-assisted heat treatment furnace and performing solution treatment in a microwave field. Before the magnesium alloy solution treatment, the interior of the furnace cavity needs to be preheated by resistance wire heating at a preheating temperature of 5°C / min.
6. The method for preparing ultrafine-grained biodegradable magnesium alloy wire according to claim 5, characterized in that: The solution treatment of the magnesium alloy material, casting or ingot is carried out in a microwave field, and the microwave application frequency is 1-3 GHz and the power is 2000-3000W.
7. The method for preparing ultrafine-grained biodegradable magnesium alloy wire according to claim 1, characterized in that: The inner wall of the extrusion die in S2 is lubricated with graphite, and the high temperature stability and low volatility of the solid lubricant can provide a better lubrication effect at high temperatures.
8. The method for preparing ultrafine-grained biodegradable magnesium alloy wire according to claim 7, characterized in that: Internal lubrication of the mold can also be achieved by applying a lubricating coating, such as molybdenum coating or titanium coating, on the mold surface to reduce contact between metal surfaces and reduce wear.